Antiviral Fluorenone Derivatives from Arundina gramnifolia - Niu, De-Yun; Han, Jing-Mei; Kong, Wei-Song; Cui, Zhu-Wen; Hu, Qiu-Fen; Gao, Xue-Mei (Asian Journal of Chemistry, 2013)
A new fluorenone derivative, gramniphenol H (1), together with four known fluorenone derivatives (2-5) were isolated from the whole plant of Arundina gramnifolia. Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. Compound 1 was tested for its cytotoxicity against five human tumor cell lines and it shows modest cytotoxicity against PC3 and SHSY5Y cell with IC50 values of 6.18 and 4.25 μM, respectively.